PENGARUH WORKING CAPITAL TURNOVER DAN CASH TURNOVER TERHADAP NET PROFIT MARGIN PADA PT AKASHA WIRA INTERNATIONAL TBK PERIODE 2014 - 2023 - Riesta Dwi Saputri; Kartono (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of working capital turnover and cash turnover on net profit margin at PT. Akasha Wira International, Tbk for the period 2014-2023. The research method used is descriptive quantitative, which describes the compan’s financial condition expressed in numerical form. Data management was processed using SPSS version 26. The result show that partially, working capital turnover does not has a significant effect on net profit margin, with tcount < ttabel is -0,120 < 2.364 and a significance value of 0.908 (0.908 > 0.05). Cash turnover, does not have a significant effect on net profit margin, with tcount < ttabel (-2,153 < 2.364) and a significance value (0.068 > 0.05).Simultaneously, working capital turnover and cash turnover have a significant effect on net profit margin, with Fcount > Ftabel (8,233 > 4.46) and a significance value (0.014 < 0.05). R square value of 0.702 indicates that the independent variabels used in the study contributed to the formation of the Net Profit Margin by 70,20%, while the remaining 29,80% is influenced by other variables outside the research model